Challenges of Power Engineering and Environment Proceedings of the International Conference on Power Engineering 2007 - Cen, Kefa.; Chi, Yong.; Wang, Fei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book is the proceedings of the International Conference on Power Engineering-2007. The fields of this book include power engineering and relevant environmental issues. The recent technological advances in power engineering and related areas are introduced. This book is valuable for researchers, engineers and students majoring in power engineering.
Invited Lecture -- Power Systems -- Fuel Utilization -- Boilers -- Turbines -- Generators -- Components, Equipments and Auxiliaries -- Operation and Maintenance -- Environmental Protection -- Heat Transfer, Combustion and Dynamics -- Fuel Cell -- Micro, Nano Heat Transfer and Flow -- Materials for Energy Systems -- Alternative Energy -- Economics of Energy System -- Numerical Simulation.
Keywords: Engineering; Energy; Electric power production; Electrical engineering; Engineering; Electrical Engineering; Energy Technology; Energy, general; Electronic books